Proposal centre of sustainable tourism from unused buildings in Zádiel - Zuzana JURKASOVA (Editura Universităţii din Oradea, 2018)
Not only around the world are many nice places which fascinate visitors, but also in our small country, in Slovakia. We have many rare human works, historical monuments, animals, plants, or minerals, which help us to make sense about nature, which is around us. It is very sad, that sometimes people know world better than their own country. In this context, it is necessary to know that all of places, not only around the world, but also at home have only limited traffic rate, which should be the base stone of sustainable development of tourism. To these areas belongs also National Park Slovak Karst, with one of the most visited part Zádiel gorge. It is famous region with many caves, ravines and limestones formations. All of mentioned should help to region be world known, what suppose many tourists here, who used to burden environment. Currently analyze does not show abnormal burden nature through tourism, but now is time thinking about protection this area and ways how to use existing options. This is the main reason why article describe analysis of burden of tourism in Zádiel area and using of existing objects to sustainable tourism.